Brief report: risk stratification following curative therapy for stage I NSCLC - Butts, Emily; Gococo-Benore, Denise; Pai, Tanmayi; Moustafa, Muhamad Alhaj; Heng, Fei; Chen, Ruqin; Zhao, Yujie; Manochakian, Rami; Lou, Yanyan (Frontiers in Oncology, 2023)
Introduction Surveillance with computed tomography (CT) imaging following curative treatment of stage I non-small cell lung cancer (NSCLC) is important to identify recurrence or second primary lung cancers (SPLC). The pattern and risks of recurrence following curative therapy and optimal duration of surveillance scans remain unknown. The objective of our study is to assess the pattern of recurrence and development of SPLC to risk stratify patients with stage I NSCLC following curative therapy. Methods We identified 261 patients who received curative therapy for stage I NSCLC at Mayo Clinic Florida. Data was collected on clinical and demographic features including gender, smoking history, stage, treatment, histologic subtype, and tumor grade. Kaplan-Meier method was used to evaluate the disease free survival (DFS). Cox proportional hazard model was used to identify risk factors for recurrence. Results Negative tobacco history and stage IA tumors were associated with significantly prolonged DFS after adjusting for co-variates (p=0.001 and p=0.005). Univariate Cox proportional hazards model identified tobacco history and stage 1B as risk factors for recurrence with unadjusted hazard ratio (HR) of 2.8 and 2.0, respectively. After adjusting for covariates, only stage IB was statistically significant predictor of recurrence with a hazard ratio of 2.1 (Confidence Interval (CI) 95% 1.2-3.6; p=0.007). Conclusions An individualized approach that considers risk factors of stage and smoking history may be useful in determining whether to continue annual CT surveillance after five years post curative therapy for stage I NSCLC.